2007
DOI: 10.1080/01140670709510201
|View full text |Cite
|
Sign up to set email alerts
|

Improving seed vigour assessment of super sweet and sugar‐enhanced sweet corn (Zea mays saccharata)

Abstract: Given the lack of comprehensive research on seed vigour of sweet corn (Zea mays saccharata) and different genetic backgrounds of super sweet and sugar-enhanced sweet corn, it is necessary to improve their seed vigour assessment. Seed vigour status of eight super sweet and eight sugar-enhanced sweet corn hybrids was examined by standard germination, stress resistance, physiological and biochemical tests, and field emergence tests. Analysis of variance showed significant differences between sweet corn genotype a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 8 publications
2
14
0
Order By: Relevance
“…Our research showed that GP did not significantly correlate with field emergence performances of Chinese fir in both years. The result was also similar to our previous study in sweet corn (Zhao et al 2007). GI represents germination speed, which is one of vigor indices.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our research showed that GP did not significantly correlate with field emergence performances of Chinese fir in both years. The result was also similar to our previous study in sweet corn (Zhao et al 2007). GI represents germination speed, which is one of vigor indices.…”
Section: Discussionsupporting
confidence: 92%
“…The DA test referred to the method of Zhao et al (2007). Ten seeds were randomly chosen and then performed on length cutting along the center of seed embryo.…”
Section: Dehydrogenase Activity Testmentioning
confidence: 99%
See 1 more Smart Citation
“…However, seeds of Shrunken-2 (sh 2 ) varieties such as Green Superman are less vigorous than the other sweet corn types due to reduced starch reserves for germination, cracked seed coats, and increased sugars which render the seed more susceptible to disease. Poor seedling establishment was the major obstacle in sweet corn production (Zhao et al, 2007). Therefore, how to improve seedling emergence has been extensively studied in super sweet corn.…”
mentioning
confidence: 99%
“…Field emergence percentage (FEP) and field emergence speed (FES) are vital indices for field performance assessment since they directly affect crop yield and quality (Zhao et al, 2007). Therefore, the effect of sand priming on improving the field emergence performance of super sweet corn was investigated.…”
mentioning
confidence: 99%